2019
DOI: 10.31234/osf.io/w6un2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual differences in logical intuitions on reasoning problems presented under two-response paradigm

Abstract: Studies on individual differences in susceptibility to cognitive biases have identified several cognitive dispositions which were thought to predict reasoning by contributing to the efficiency of analytic thought. Recently formulated hybrid models, however, suggest that substantial differences between reasoners may arise early already in the intuitive stages of the reasoning process. To address this possibility, we examined standard individual difference measures, mindware instantiation, and conflict detection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Also, the fact that detection efficiencies did show up to predict conflict reasoning accuracy over standard individual difference predictors and mindware instantiation suggests that detection indices did capture some meaningful variance which is predictive of reasoning performance and is not due to other related cognitive factors which were included in the analysis. Most importantly, a recent study by Burič and Šrol (2019) offers some evidence for the replicability of the present conflict detection findings and thus lends further credence to the results we report here.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, the fact that detection efficiencies did show up to predict conflict reasoning accuracy over standard individual difference predictors and mindware instantiation suggests that detection indices did capture some meaningful variance which is predictive of reasoning performance and is not due to other related cognitive factors which were included in the analysis. Most importantly, a recent study by Burič and Šrol (2019) offers some evidence for the replicability of the present conflict detection findings and thus lends further credence to the results we report here.…”
Section: Discussionsupporting
confidence: 88%
“…Still, it is possible that a simple solution such as increasing the number of neutral items might help researchers in future studies to limit the problem of low internal consistency and thus increase the reliability of findings pertaining to the role of the mindware component in the reasoning process. Although the mindware instantiation in our study showed up to be the most substantial predictor of both conflict detection and overall accuracy on conflict reasoning problems, due to low reliability of our mindware measure, the results will have to be taken with some caution (although, for similar patterns of results pertaining to mindware instantiation, see Burič & Šrol, 2019).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, this assumption needs to be further analyzed in future research, as it is not supported by relevant data. Second, there is not much research combining the CRT with the two-response paradigm, as most of the studies have been using syllogisms, conditional reasoning tasks or base-rate neglect tasks (Bago & De Neys, 2017;Burič & Šrol, 2019;Thompson et al, 2011;Thompson & Johnson, 2014), with an exception of Bago and De Neys (2019b), who used the bat-and-ball problem, but not the rest of the CRT. Thus, we are not provided with a relevant benchmark.…”
Section: Discussionmentioning
confidence: 99%